Family Planning from the Perspective of Official State Interpretation - Mubarok, Muhammad Luthfi; Baehaki, Ahmad; Sadali, Achmad Dafid Imron (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Family planning remains a debated topic in Muslim societies, balancing between the Islamic emphasis on procreation and the obligation to preserve maternal health and family welfare. Specific Background: In Indonesia, the government promotes family planning through the National Population and Family Planning Agency, yet religious interpretations continue to shape societal acceptance. The Tafsir Ilmi Seksualitas dalam Perspektif Al-Qur’an dan Sains, an official state exegesis, offers a unique integration of Qur’anic principles and scientific reasoning. Knowledge Gap: Despite extensive discourse on family planning in Islamic law, few studies analyze its interpretation within Indonesia’s official government exegesis. Aims: This study investigates the concept of family planning in the state-sanctioned Scientific Exegesis of Sexuality in the Perspective of the Qur’an and Science to understand how it reconciles religious doctrine and modern scientific insights. Results: Findings reveal that the exegesis permits family planning as long as it prevents harm, drawing on verses such as Al-Baqarah (2:233) and An-Nisa (4:9) and acknowledging methods like ‘azl, condoms, IUDs, and hormonal contraceptives. Novelty: This study offers the first systematic analysis of family planning through Indonesia’s official Qur’anic interpretation. Implications: The results affirm that family planning aligns with Islamic principles of welfare (maslahah), providing theological legitimacy for national health policies. Highlights: Integrates Qur’anic teachings with modern science in state-sanctioned interpretation. Affirms permissibility of family planning for maternal and family welfare. Provides theological support for Indonesia’s national health policy. Keywords: Family Planning, Islamic Exegesis, Qur’anic Interpretation, Reproductive Health